2018
DOI: 10.3389/fnbeh.2018.00233
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Mediates Depression of Aggression After Acute and Chronic Social Defeat Stress in a Model Insect

Abstract: In all animals, losers of a conflict against a conspecific exhibit reduced aggressiveness, often coupled with depression-like symptoms, particularly after multiple defeats. While serotonin (5HT) is involved, discovering its natural role in aggression and depression has proven elusive. We show how 5HT influences aggression in male crickets, before, and after single and multiple defeats using serotonergic drugs, at dosages that had no obvious deleterious effect on general motility: the 5HT synthesis inhibitor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…It is demonstrated that 5HT depresses aggressiveness in subordinate cricket after agonistic interaction. (Rillich and Stevenson, 2018). It is demonstrated that synaptic responsiveness to 5HT changes with social status in crayfish (Yeh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that 5HT depresses aggressiveness in subordinate cricket after agonistic interaction. (Rillich and Stevenson, 2018). It is demonstrated that synaptic responsiveness to 5HT changes with social status in crayfish (Yeh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Some signatures of mild stress, such as cognitive arousal and resistance to threatening stimuli resemble the effects of motor load in mammals as well as in snails (Kavaliers, 1987;Heijnen et al, 2016). Numerous observations associate serotonin with stress-induced behavior in vertebrates and invertebrates (Shartau et al, 2010;Bacqué-Cazenave et al, 2017;Rillich and Stevenson, 2018). On the other hand, the behavioral and neurochemical effects differ between the exerciseinduced stress and stress due to "negative life events" in mammals (Heijnen et al, 2016).…”
Section: Intense Locomotion And/or Stress?mentioning
confidence: 99%
“…In contrast, incubation in serotonin may result in less specific action on various serotonin and monoamine receptors. 5-HTP is more effective than serotonin in many other experimental models: a variety of gastropod mollusks (for review, see Sakharov, 1991); crickets (Ureshi et al, 2002;Dyakonova and Krushinsky, 2013;Rillich and Stevenson, 2018); locust (Anstey et al, 2009). Neither serotonin in any concentration nor its metabolic precursor affected the orienting phase of the behavior (the rotation prior to decision-making).…”
Section: Serotonin and Behavioral Changes Caused By Preceding Intensementioning
confidence: 99%
“…Nymphs are, however, aggressively intimidated by adult males (Fig 1), on average about once an hour in grouped nymph-adult colonies (Fig 6B), and this has long lasting behavioural consequences. In adult crickets, repeated hourly defeats induce long-term depression of aggression that can last for days [16,17]. Similarly, nymphs raised with adult males are significantly less active and less aggressive weeks later when they become adult, in comparison to adults with no contact to adult males during nymphal life (Fig 6C and 6D).…”
Section: Discussionmentioning
confidence: 87%
“…From studies to date it remains unclear, whether competition between nymphs establishes dominant-subordinate relationships as in adults, with potentially long lasting consequences for an individual´s future behaviour. As in most animals [13], adult male crickets that win an agonistic encounter are subsequently more aggressive [14], whereas losers become submissive [15][16][17]. Moreover, winners tend to have a more active behavioural profile than losers [18][19][20], which points to agonistic experience, in adults at least, as a prime determiner of consistent inter-individual behavioural differences in crickets [19,21].…”
Section: Introductionmentioning
confidence: 93%